2009
DOI: 10.11606/issn.2176-7262.v42i3p366-371
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização da perda auditiva de crianças atendidas em um programa de saúde auditiva

Abstract: Objetivo: caracterizar a perda auditiva de crianças avaliadas e atendidas no Programa de Saúde Auditiva do Hospital das Clínicas de Ribeirão Preto. Metodologia:   Aprovado no Comitê de Ética do Hospital das Clínicas de Ribeirão Preto da Universidade de São Paulo. Estudo retrospectivo em uma amostra de 279 prontuários de crianças na faixa etária entre 2 a 12 anos de idade, atendidas no período de outubro de 2001 a agosto de 2005, sendo selecionados para a análise de resultados 133 casos que tiveram a confirmaçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
0
4
0
3
Order By: Relevance
“…Sensorineural hearing loss had the greatest prevalence, which was also observed in public hearing health programs in Santa Maria (RS) 15 , Montes Claros 17 , Florianópolis (SC) 22 , Ribeirão Preto (SP) 19 , São Paulo (SP) 18 and a predominance of moderate hearing loss is supported by studies from Monte Negro (RO) 4 , Santa 23 , a study also found that, due to insufficient financial resources, this population was not able to utilize PSAP until the establishment of Hearing Health Care Services.…”
Section: Discussionmentioning
confidence: 89%
“…Sensorineural hearing loss had the greatest prevalence, which was also observed in public hearing health programs in Santa Maria (RS) 15 , Montes Claros 17 , Florianópolis (SC) 22 , Ribeirão Preto (SP) 19 , São Paulo (SP) 18 and a predominance of moderate hearing loss is supported by studies from Monte Negro (RO) 4 , Santa 23 , a study also found that, due to insufficient financial resources, this population was not able to utilize PSAP until the establishment of Hearing Health Care Services.…”
Section: Discussionmentioning
confidence: 89%
“…The most common causes are related to very low birthweight (under 1,500g), hyperbilirubinemia, congenital infections such as rubella, toxoplasmosis, cytomegalovirus, syphilis and contact with ototoxic drugs in the neonatal period, in addition to congenital malformations of the head and/or neck, or syndromes (14) . A retrospective study (2) with 133 children between 2 and 12 years old identified that the most frequent risk factors for hearing loss were family complaints of delayed acquisition and development of speech and language or hearing problems (22.56%), otitis media that is recurring or persists for more than three months (22.56%), use of ototoxic drugs (19.55%), neonatal ICU stay for 48 hours or longer (14.29%), and congenital infections (12.78%). Regarding the type of loss, sensorineural prevailed (66%), with bilateral hearing loss presenting the greatest degree (26.3%).…”
Section: Discussionmentioning
confidence: 99%
“…To minimize the effects of delayed diagnosis and treatment, a Universal Neonatal Hearing Screening (2,14,15) is possible with guidance for parents regarding child development so that they can be attentive to the occurrence of hearing alterations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O grande número de artigos publicados se mantém em 2010, assim como a variedade dos temas abordados. Aparecem pela primeira vez artigos sobre o perfil dos usuários 7,8 , trazendo descrições socioeconômicas, demográficas e das perdas auditivas de sujeitos atendidos em serviços credenciados. Outro tema inédito é a construção de indicadores de saúde em saúde auditiva 22 , por meio de questionário sobre o serviço.…”
Section: Figura 4 -Quadro Resumo Com Os Artigos Do Eixo Temático Serviçounclassified